2018
DOI: 10.1177/1753193418783330
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dart thrower’s range of motion following radioscapholunate fusion, four-corner fusion and proximal row carpectomy

Abstract: Dart thrower's motion is the functional coupled movement of the wrist from radial extension to ulnar flexion. The aim of this study was to evaluate dart thrower's motion following three surgeries: radioscapholunate fusion, four-corner fusion and proximal row carpectomy. Six fresh-frozen cadaver forearms were dissected. Sequential loading of tendons resulted in radial extension and ulnar flexion allowing dart thrower's motion measurements at end range before and then again after each surgery. After radioscaphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…In contrast, we found that the patients after RSL fusion had significantly reduced ROM during DTM compared with the patients after MF. Our findings are supported by two cadaver studies, which found no significant differences in the DTM after RSL and MF (Kane et al., 2018; Rust et al., 2018). Kane et al.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, we found that the patients after RSL fusion had significantly reduced ROM during DTM compared with the patients after MF. Our findings are supported by two cadaver studies, which found no significant differences in the DTM after RSL and MF (Kane et al., 2018; Rust et al., 2018). Kane et al.…”
Section: Discussionsupporting
confidence: 87%
“…Partial wrist fusion is frequently carried out with the aim of reducing pain at the radiocarpal and midcarpal joints and maintaining the best possible wrist function. However, previous studies investigating the effect of simulated partial wrist fusions on DTM have been done only on cadavers (Calfee et al., 2008; Kane et al., 2018; Rust et al., 2018). The effects of limited mobility on wrist kinematics during functional movements have not yet been investigated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Three individual Kessler sutures of 3-0 Prolene (Ethicon®, Somerville, NJ, USA) were stitched into each tendon, to grasp the tendon ends. A specially designed frame (Rust et al., 2018) was used. The specimens were fixed by the clamp on the radius, orienting the specimens vertically, with the fingers dependant and ensuring that the wrist was hanging freely, thus removing the effects of gravity.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, these biomechanics declare as well that after PWF the wrist is compromised due to the increased compressive forces in the surrounding intercarpal joints which is to be considered generally as a predisposition for secondary OA [22]. Furthermore, due to the coupled motion between extension-flexion and radial-ulnar deviation [23], impaired wrist extension-flexion inevitably can lead to impairment of "dart-throwing" motion [24], but it is not always observed after radiocarpal fusion, 4CF, and PRC [25]. PRC (i.e.…”
Section: Which Salvage Procedures Exist and Which Wrist Motion Is Neementioning
confidence: 99%